Tetrahydrobiopterin, the cofactor for aromatic amino acid hydroxylases, is synthesized by and regulates proliferation of erythroid cells. - Tanaka, K (1989)
The only known role for 6(R)-5,6,7,8-tetrahydrobiopterin (BH4) is as the cofactor for the aromatic amino acid hydroxylases. However, BH4 has been shown to be synthesized by cells that do not contain any hydroxylase activity, suggesting that it may have still undiscovered functions. Our finding of much higher levels of BH4 and GTP cyclohydrolase, the first enzyme of de novo BH4 biosynthesis, in rat reticulocytes compared to mature erythrocytes raised the possibility that BH4 might play a role in erythrocyte maturation. We have now demonstrated, by using murine erythroleukemia (MEL) cells as a model for erythrogenesis, that BH4 synthesis is required for proliferation of these cells. Inhibition of BH4 biosynthesis in rapidly dividing MEL cells with N-acetylserotonin, a potent inhibitor of sepiapterin reductase, the terminal enzyme in the BH4 biosynthetic pathway, results in inhibition of DNA synthesis and mitogenesis without induction of hemoglobin synthesis. The inhibition of DNA synthesis is reversed by repletion of cellular BH4 levels with sepiapterin, a pterin that is readily taken up by the cells and converted to BH4 by the sequential reductions of sepiapterin reductase and dihydrofolate reductase. Treatment of MEL cells with hexamethylene bisacetamide, an inducer of differentiation, results in a decrease in BH4 synthesis accompanied by a cessation of growth and concomitant hemoglobin synthesis. The inhibition of proliferation induced by hexamethylene bisacetamide can be reversed by maintaining high intracellular levels of BH4, which also decreases the amount of hemoglobin. The mechanism of the BH4 effect has not yet been elucidated, but it appears as though BH4 synthesis is more intimately linked with cell proliferation than with the differentiation process.